Factors Influencing Millennials Purchase Intention - Gina Fitriana; Robert Kristaung (STIE-JIC, 2020)
This study examines the effect of attitude, subjective norms, deal proneness and reciprocity toward purchase intention through subjective norms. The purposive sampling method was used to obtain data from 190 consumers of Starbucks through Line social media and the company’s official account and analyzed using the Structural Equation Modelling (SEM) and the Analysis of Moment Structure (AMOS) program. The result showed that (1) deal proneness positively influence attitude, (2) attitude has a positive influence on purchase intention, (3) reciprocity positively influence subjective norms, (4) subjective norms has a positive influence on purchase intention, (5) deal proneness positively influence purchase intention through attitude, and (6) reciprocity has a positive influence on purchase intention through subjective norms.